Hate Speech against Javanese in Social Media: A Case Study of Instagram Platform - Tengku Abdillah Azis; Cindy Melissa Wijaya; Maria Joito Gultom; Muhammad Alfi Harahap; Ridho Amalan Saufi Sipahutar; Tumiar Sidauruk (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the phenomenon of hate speech against the Javanese ethnic group on the Instagram platform, reflecting inter-ethnic tensions in Indonesia. Such hate speech appears in the form of negative stereotypes, verbal insults, and anti-migrant sentiments, triggered by perceptions of Javanese dominance in social, economic, and political sectors. Using a descriptive qualitative approach with a case study method, data were collected through documentation of Instagram posts and comments, as well as interviews with both perpetrators and victims. The findings reveal that hate speech is driven by historical grievances, social jealousy, and a culture of humor that belittles others. Its impacts include psychological harm to victims and the potential for social division. The lack of regulation on social media exacerbates the spread of hate speech. Therefore, public education and the promotion of inclusive communication are essential to encourage tolerance and strengthen social cohesion in digital spaces. This study aims to contribute to the field of digital communication and support policy development related to diversity in the social media era.